Digital Provenance and the Artwork as Derivative - Wark, McKenzie (post(s), 2017)
Art is about rarity, about things that are unique and special and cannot be duplicated. Yet the technologies of our time are all about duplication, about copies, about information that is not special at all. At first, it might appear that the traditional form of art is obsolete. If it has value, it is as something from a past way of life, before information technology took over. Yet, what appears to be happening is even stranger. Let us examine some of the special ways in which art as rarity now interacts in novel ways with our abundant sources of information, producing some rather striking opportunities to create value.
Keywords: contemporary art; rarity; technology; derivative